The effect of growth temperatures and substrate orientations of indium gallium phosphide quantum wires - Nor Hamizah Nor Helmi, 1989- author; Zulkafli Yusoff, supervisor; Fakulti Sains (2014)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2014